CODESRIA Bulletin Online, No. 14, June 2021: Higher Education in a Post-COVID-19 World: Challenges and Opportunities for African Universities - Zeleza, Paul Tiyambe (CODESRIA Bulletin, 2021)
The COVID-19 pandemic has exposed and exacerbated the systemic deficiencies and inequalities in health care systems, economies, businesses and educational institutions around the world. African universities have been particularly affected. What does this portend for their future and for the production, consumption and dissemination of scholarly knowledges? In this article, I argue that universities face various alternative and overlapping futures ranging from restoration, to evolution, to transformation. These interlinked scenarios encompass every aspect of university affairs from the modalities of teaching and learning, financial models, leadership skills, and institutional governance systems to modes of external engagements. In this context, it is critical to interrogate the desirable transformative trajectories for African universities. Constructing new futures for African universities and knowledge economies entails institutional, intellectual and ideological struggles and negotiations, and different ways of studying and assessing the value proposition of universities not only for students and other internal stakeholders, but also for African societies and diasporas in their complex national and transnational dimensions, articulations and intersections. As an historian, I trust you will appreciate it if I begin by revisiting the agenda for African higher education set at the First African Higher Education Summit held in Dakar, Senegal, in March 2015. The summit identified the challenges and opportunities for African universities in the realisation of the African Union’s Agenda 2063, which remain as pressing as ever; indeed, it is even more imperative in the forthcoming post-COVID-19 world. Secondly, I briefly review the challenges exposed and exacerbated by the pandemic. Finally, I outline the agenda for reform and transformation in four key areas: digitalisation, leadership, institutional cultures, and financing. Revisiting the agenda of the Dakar summit The African Union’s Agenda 2063, provides ‘a blueprint and master plan for transforming Africa into the global powerhouse of the future. It is the continent’s strategic framework that aims to deliver on its goal for inclusive and sustainable development and is a concrete manifestation of the pan-African drive for unity, self-determination.’2 Education is indispensable for the realisation of Agenda 2063 in so far as promoting integrated, inclusive, innovative, structural and sustainable development requires building strong human capital, research systems, and robust collective identities and civic values.3 The Dakar summit sought ‘to create a continental multi-stakeholders’ platform to identify strategies for transforming the African higher education sector’ in pursuit of Agenda 2063. I was commissioned to write the Framing Paper for the summit and help draft the Declaration and Action Plan.4 In the paper, I provided a broad overview of the historical development of African higher education from ancient times to the colonial era to the post-independence period. The latter is characterised by three trends, namely: expansion, crisis and reform. In 1959, on the verge of Africa’s ‘year of independence’ in 1960, when seventeen countries achieved their freedom from colonial rule, there were only seventysix universities across Africa mostly concentrated in South Africa, Egypt, and parts of West Africa. The number rose to 170 in 1970, 294 in 1980, 446 in 1990, 784 in 2000, 1,431 in 2010, and 1,682 in 2018. Enrolments rose from 0.74 million in 1970 to 1.7 million in 1980, 2.8 million in 1990, 6.1 million in 2000, 11.4 million in 2010, and 14.7 million in 2017. As rapid as this growth was, Africa remained with the lowest levels of higher education institutions and tertiary enrolments, which stood at 8.9 per cent of the world’s 18,772 higher education institutions (Asia had 37 per cent, followed by Europe with 21.9 per cent, North America 20.4 per cent, Latin America and the Caribbean 12 per cent), and 6.6 per cent of the world’s 220.7 million students. Forty-five per cent of the African students were in North Africa. To put it more graphically, Indonesia had nearly as many students in higher education institutions as the whole of sub-Saharan Africa (7.98 million compared to 8.03 million). Enrolment ratios tell the story differently. In 2017, the world’s average enrolment ratio was 37.88 per cent, compared to 8.98 per cent in sub-Saharan Africa and 33.75 per cent in North Africa. Kenya’s stood at 11.66 per cent in 2016. For high-income countries it was 77.13 per cent, for upper-middleincome countries 52.07 per cent, for middle-income countries 35.59 per cent, and lower-middle-income countries 24.41 per cent. The proverbial development case of South Korea is instructive. As pundits never tire of pointing out, in 1960 the country’s level of development was comparable to that of some African countries, yet its enrolment rate in 2017 was 93.78 per cent! And China, the emerging colossus of the world economy, had a rate of 51.01 per cent. Put simply, not enough Africans are going to university. The second trend I discussed in the Framing Paper was the massive crisis of structural adjustment in the lost decades of the 1980s and 1990s. The rationales and models that had undergirded them changed in the maelstrom of the world economic crisis and the rise of neoliberalism following the end of the long global post-war boom and the demise of the Keynesian welfare state in the global North and the developmental state in the global South. The impact on African higher education was devastating. It was expressed in declining state funding, falling instructional standards, declining facilities, shrinking wages, and low faculty morale. Academics increasingly resorted to consultancies or they became part of the ‘brain drain’ as they sought refuge in other sectors at home or universities abroad. This was followed by the third trend from the 2000s as many African economies resumed the growth of the early post-independence years and democratisation spread as struggles for the ‘second independence’ intensified. The reform agenda raised and focused on seven sets of issues that I cannot elaborate on here because of time constraints. First, there was the need to re-examine the philosophical foundations and nationalist objectives of African higher education in an era of neoliberalism and knowledge economies. Second, African higher education institutions were confronted with the question of how to deal with their changing demographics and demands for equity, diversity and inclusion based on the social inscriptions of gender, ethnicity, class, religion, etc. Third, the question of privatisation and its effects rose to the top of the policy and public agenda as public institutions were increasingly privatised, private institutions exploded and overtook public ones, and for-profit-institutions expanded. Fourth, the challenges of governance and accountability became increasingly apparent. Fifth, financial pressures intensified as public funding declined, cost-sharing measures were developed, and conditions of work in terms of salaries declined forcing faculty to indulge in income generation activities including consultancies and adjuncting. The result was low research productivity, poor staff morale, institutional conflicts, and declining quality of education. Many African universities became glorified high schools. Sixth, demands grew for accountability through the quality assurance movement from the ever expanding stakeholders of higher education. Finally, the perennial struggle between indigenisation and internationalisation for Africa’s higher education institutions and knowledge production systems entered a new phase as globalisation accelerated. The paper noted some of the key global developments African universities had to grapple with. Four stood out. First, was the unbundling of the systems developed after World War II including the erosion of universities’ monopoly over research and credentialing as new entrepreneurial providers and research institutions sponsored by business, non-governmental organisations and other agencies emerged. Second, was the disruptive and transformative impact of technology in all aspects of university activities from teaching to research, to operations and provision of services. Third, there were fundamental shifts taking place in the global political economy in terms of hegemonies and hierarchies and in the nature and future of jobs that challenged traditional curricula and pedagogies. Fourth, new forms of intraand interinstitutional competition and collaboration were emerging within and across countries, increasingly sanctified and reproduced by rankings that regulated global academic capitalism. I made six recommendations for the summit. First, how to match growth, or massification, with quality. Second, strategies for improving financing and management. Third, how to promote the articulation, harmonisation and quality assurance in Africa’s higher education systems that needed greater horizontal and vertical differentiation and diversification. Fourth, modalities to promote institutional autonomy and improve governance. Fifth, enhancing research and innovation. Sixth, strengthening beneficial internationalisation and diaspora mobilisation. These recommendations found their way into the Summit Declaration and Action Plan, which identified eight priorities. I will quote each priority as described in the heading. We call for an ambitious commitment of various stakeholders to expand higher education, including, achieving through concomitant investments in academic staff, infrastructure, and facilities by the state, private sector, and society at large, a higher education enrolment ratio of 50%. Promote diversification, differentiation and harmonisation of higher education systems at the national, institutional and continental/regional levels by African countries to enable consolidation and assure the quality of educational provision against locally, regionally and internationally agreed benchmarks of excellence. Increase investment in higher education to facilitate development, promote stability, enhance access and equity; develop, recruit and retain excellent academic staff and pursue cutting-edge research and provision of high quality teaching. Appropriate investments are required at institutional, national, regional and international levels. African higher education institutions shall commit themselves to the pursuit of excellence in teaching and learning, research and scholarship, public service and provision of solutions to the development challenges and opportunities facing African peoples across the continent. Key actions are required by all stakeholders and levels to assure quality, relevance and excellence. Commit to building capacity in research, science, technology and innovation. Pursue national development through business, higher education and graduate employability: despite the rapid expansion of higher education enrollments, there are serious concerns about the ability of Africa’s universities to produce the kinds of graduates who can drive the continent forward. Nation building and democratic citizenship: as enshrined in the relevant sections of African Charter on Human and Peoples Rights, 1981 and in the AU’s Agenda 2063, the continent seeks to deepen the culture of good governance, democratic values, gender equality, respect for human rights, justice and the rule of law. Mobilise the diaspora: develop a 10/10 programme that sponsors 1,000 scholars in the African diaspora across all disciplines every year, for ten years, to attend African universities and colleges for collaboration in research, curriculum development, and graduate student teaching and mentoring. Challenges exposed and exacerbated by the pandemic The outbreak of the coronavirus pandemic in early 2020 forced universities around the world to confront unprecedented challenges that simultaneously exposed and exacerbated existing deficiencies and dysfunctions. Six stand out. First, in terms of transitioning from face-to-face to remote teaching and learning using online platforms. Second, managing severely strained finances. Third, ensuring the physical and mental health of students, faculty and staff. Fourth, reopening campuses as safely and as effectively as possible. Fifth, planning for a sustainable post-pandemic future. Sixth, contributing to the capacities of government and society in resolving the multiple dimensions of the COVID-19 pandemic. Universities in Africa were among the most affected and least able to manage the multi-pronged crises because of their pre-existing capacity challenges that centred on ten dimensions, namely: institutional supply, financial resources, human capital, research output, physical and technological infrastructures, leadership and governance, academic cultures, quality of graduates, patterns of internationalisation, and global rankings. The first refers to the inadequate number of universities on the continent noted earlier. The second concerns inadequate financing, declining public investment, and limited philanthropic support for higher education. The third is about the insufficient availability of faculty and lessening attractiveness of academic careers because of the devaluation of academic labour. The fourth points to low levels of research funding and productivity. The fifth alludes to the poor state and maintenance of physical and technological infrastructures. The sixth touches on external interference and politicisation of university executive appointments, corporatisation, and lack of leadership development opportunities. The seventh suggests growing social conflicts with the pluralisation of internal and external constituencies and erosion of academic freedom. The eighth signifies persistent mismatches between graduates and the needs of the economy that result in high levels of unemployability. The ninth implies the durability of coloniality, intellectual dependency, and unequal international engagements. The tenth indicates the low standing of African universities in world rankings, notwithstanding the problems with rankings as instruments of global academic capitalism. Some of these institutional deficits directly affected the ability of universities to manage the pandemic and plan for the post-pandemic future. Most crucial are the technological, financial and research capacities, and the state of institutional cultures and leadership. Many African universities suffered from limited digital infrastructure, capacity and connectivity, which made it difficult for them to transition online for education, research and administration. The digital divide was evident among and within countries and institutions in terms of access to broadband, electronic gadgets, data costs, digital literacy and preparedness for administrators, faculty, staff and students. Digital inequalities reflected and reinforced the prevailing differentiations of class, gender, age, race, location, disability, and other social markers. The technological challenges were compounded by worsening financial strains. University revenues from auxiliary services plummeted following campus closures; student enrolments and ability to pay tuition dropped sharply as economies went into recession and unemployment for parents or guardians rose; government funding declined; and philanthropic donations fell and were increasingly diverted to emergency health care. Universities were forced to undertake severe budget cuts including job furloughs, reductions in salaries and pensions, suspension of capital projects and renegotiation of service contracts. Some stared at the brink of bankruptcy and permanent closure. Under such circumstances new investments in electronic infrastructures were difficult to support and sustain. The financial crisis was of course not confined to African or developing countries. It was a global phenomenon as is evident in numerous reports from UNESCO, the European University Association, International Association of Universities, Association of Commonwealth Universities, and African Association of Universities. Depressing stories about the loss of millions of jobs in universities and other draconian cost containment measures including salary reductions, suspension of pensions and other benefits, increased workloads, merging and elimination of some departments, outsourcing of more and more services were blared across the academic and national media in developed and developing countries alike such as – to mention those that I read every day – University World News, Times Higher Education, Chronicle of Higher Education, Inside Higher Education, New York Times, Washington Post, Wall Street Journal, the Guardian, and closer to home in Kenya the Daily Nation and the Standard. Similar reports have been produced by consultancy services such as McKinsey, Ernest & Young, and Moody’s. The pandemic not only put pressure on African universities’ finances and operations, but also raised the stakes for research and policy interventions. Universities were expected to undertake biomedical and socioeconomic research to manage the pandemic. As I noted in an article in University World News summarising a series of webinars by the Alliance for African Partnership that I moderated between April and July 2020, some universities produced hygiene products and personal protective equipment including hand sanitizers, masks, ventilators, EpiTents for patient isolation and mobile hospitals, testing kits, and robots for delivery of food and medicines to patients. Others undertook research on the epidemiology of the coronavirus and biomedical treatments, and on the socioeconomic impacts of the pandemic, provided advisory services to government, developed software to monitor the pandemic’s spread, and sought to raise awareness and provide psychosocial support to their constituents and wider society.5 However, most African universities and firms stood on the sidelines as their societies waited for the development of vaccines in the global North, China and India. At best, a few collaborated with overseas universities, research establishments and networks, and hosted clinical trials, although they were ‘unable to secure a fair pricing agreement’. Weak research and drug manufacturing capabilities have made African countries vulnerable to vaccine nationalism in the global North, while democratic deficits have led to the securitisation of mitigation measures gravely undermining human rights in several countries.6 As of May 26, 2021 doses administrated per hundred people range from more than 100 per cent in thirteen countries, to 90 per cent in the UK, 86 per cent in the US, 56 per cent in Canada and 54 per cent in Germany. African countries have the lowest rates of vaccination, ranging from less than one in a hundred in eighteen countries, one in a hundred in seven countries, two per hundred in eight countries, and three per hundred in seven countries. This is a monumental and global scandal of deadly proportions. What are our universities, governments and industries doing to serve and save themselves besides stretching their hands and praying for salvation from the rich world instead of indulging in perennial and petty, but often vicious, national and institutional politics?7 COVID-19 should be a wake-up call to African universities and countries to strengthen their research capacities, science, technology and innovation systems, manufacturing capabilities, and inter-institutional and interdisciplinary collaboration through existing consortia, such as the African Research Universities Alliance, and new ones.8 Beyond being involved in quality control and having an important role to protect the continent ‘from being used as a testing lab for COVID-19 vaccines’, some believe African universities ‘should join forces with the pharmaceutical industry and funding organizations to manufacture COVID-19 vaccines in the continent’.9 Funding for research by governments, the private sector and the universities, and collaborations among the three need to be enhanced. Despite innovations made in some universities, ‘the scale of collaboration with the industry that takes headline-making innovation beyond the walls of an institution is conspicuously missing. These collaborations can also provide an opportunity for further validation, and a path to widespread adoption and commercialization’.10 The comparative research data should be of concern to us all. In 2013, Africa accounted for 2.4 per cent of world researchers, compared to 42.8 per cent for Asia, 31.0 per cent for Europe, and 22.2 per cent for the Americas. In terms of scientific publications, Africa’s share was 2.6 per cent in 2014, compared to 39.5 per cent for Asia, 39.3 per cent for Europe, and 32.9 per cent for the Americas. For research and development (R&D) as a percentage of GDP Africa spent 0.5 per cent compared to a world average of 1.7 per cent and 2.7 per cent for North America, 1.8 per cent for Europe, and 1.6 per cent for Asia. Africa accounted for a mere 1.3 per cent of global R&D. Agenda for reform and transformation A crisis, as the saying goes, is the flip side of opportunity. The bigger the crisis, the more profound the lessons to be learned, and the greater the imperatives for transformation. African universities are likely to pursue three scenarios. The restore scenario will be focused on reclaiming the institutions’ prepandemic financial health and operations, while the evolve scenario applies to ‘institutions that will choose to incorporate the impact and lessons of the pandemic into their culture and vision’, and under the transform scenario institutions will ‘use the pandemic to launch or accelerate an institutional transformation agenda’.11 For some universities what is at stake is survival, for others stability, and for many sustainability. Institutional survival is a precondition for stability which is essential for sustainability. Confronting the entire higher education sector is the question of its raison d’être, its value proposition in a digitalised world accelerated by COVID-19. I would like to focus on four critical dimensions: promoting progressive digital transformation, effective leadership, strong institutional cultures, and sustainable funding for African universities. For the first two I propose a dozen strategies for each, and for the latter two seven strategies for each respectively. Given the limitations of time, here I only give broad outlines of the various proposed initiatives. As a scholar of intellectual history – the history of ideas and knowledge producing institutions – I’m only too aware knowledge production is framed by certain crucial dynamics, what I call the 4Is: first, intellectual, which refers to the prevailing paradigms; second, ideological, in terms of the dominant and competing ideologies at a given moment; third, institutional, as far as the nature and organisation of an institution is concerned; and finally, individual, one’s social biography with reference to gender, race, nationality, class, religion, politics, etc. Institutional change occurs in the intersections of these dynamics, out of concrete social struggles within and outside the academy, among the university’s ever expanding and shifting constituencies. Change, in short, does not emanate from analytical prescriptions or rhetorical declarations, however compelling. However, constructing desired futures is not a wasteful exercise; it can inspire action for ideas constituting an indispensable part of praxis. In a forthcoming paper I co-author with Paul Okanda, USIU’s ICT director, in the Journal of African Higher Education, whose abridged version appeared in University World News on February 11, 2021, a twelve-point agenda is proposed for the digital transformation of African universities. First, they need to embed digital transformation in institutional culture, from strategic planning, through organisational structures, to operational processes. Second, invest in digital infrastructure by rethinking capital expenditures that historically favoured physical plants. Third, develop online design competencies both individually and through consortia. Fourth, entrench technology-mediated modalities of teaching and learning encompassing face-to-face, blended, and online. Fifth, embrace pedagogical changes in terms of curricula design and delivery that involve students as active participants in the learning process rather than as passive consumers. Sixth, develop holistic and innovative curricula that impart skills for the jobs of the twentyfirst century. Seventh, adopt and use educational technologies that support the whole student for student success going beyond degree completion. Eighth, develop effective policies and interventions to address the digital divide and mental health disorders and learning disability. Ninth, as learning and student life move seamlessly across digital, physical and social experiences, universities must safeguard data protection, security and privacy. Tenth, in so far as the market for online programmes is transnational, universities must pay special attention to international students who face unique barriers. Eleventh, they should develop meaningful partnerships with external constituencies and stakeholders, including digital technology and telecommunication companies to close the glaring employability gap. Twelfth, universities will increasingly be expected to anchor their research and innovation in the technological infrastructure that supports and enhances the opportunities of the Fourth Industrial Revolution for Africa. As for effective leadership, I also see twelve areas for improvement.12 The multi-pronged health, economic, financial and social crises of COVID-19 have underscored the importance of strategic and smart institutional leadership at all levels. First, it requires ensuring that appointments for institutional heads and governance boards are based on verifiable leadership competencies, passion and understanding of the higher education sector. All too often, their selection reflects misguided political considerations, expectations of donations which are hardly honoured in African universities, or preferences for alumni wedded to institutional nostalgia and stasis. Second, university leaders at all levels from department chairs to deans, vice-chancellors to board members, must undergo periodic leadership development training specifically tailored for higher education. Third, university leaders must possess and sharpen their financial acuity. In addition to managing complex institutional budgets, they now need to develop ability to manage reductions in staffing, programmes and space. Fourth, cultural competency is more critical than ever. University leaders must go beyond making statements on valuing diversity and inclusion and articulate and exhibit deeper awareness of systemic injustice, inequality and privilege and show boundless compassion and commitment for promoting an inclusive institution. Fifth, they must display technological deftness. In an increasingly digitalised academy, it’s no longer enough for university leaders to be comfortable using emerging technologies but to model and promote institutional technological saviness and competence, and develop analytics expertise to promote datadriven decision-making. Sixth, the pandemic has shown that crisis management is essential. Besides preparing for traditional natural and security threats, leaders are currently forced to manage physical and mental health crises, emergency preparedness and business continuity, and lead in times of uncertainty. Seventh, leaders need an entrepreneurial mindset. More than ever universities want leaders who are calculated risk-takers, innovative entrepreneurs, and effective in promoting the university mission as they create beneficial external partnerships and revenue generation initiatives. Eighth, political saviness is an important asset as university leaders are increasingly required to work in uncertain and politically polarised times at national, regional and global levels that challenge them to pursue and promote advocacy and institutional discourse that is calm, informed and respectful. Ninth, empathy and respect are essential as mental stress and financial insecurity rise among university constituencies. Leaders are expected to demonstrate empathy and respect for all their internal constituencies. They must reveal their humanity, even in decisionmaking. Tenth, multi-genre communication skills are indispensable. Further to strong written and verbal communication skills, leaders are increasingly expected to provide efficient, timely, clear and persuasive messages and stories to diverse constituencies using multiple platforms including social media. Eleventh, possessing high emotional intelligence is a must. Additional to the ability to demonstrate confidence and empathy, leaders are expected more and more to demonstrate self-awareness, selfregulation, motivation, and social skills, rather than egotism, impulsivity, and proneness to bullying and micromanagement. Finally, agility is necessary. On top of wellestablished professional knowledge and experience, success increasingly depends on a leader’s ability to be flexible in the face of many changes, have the capacity to learn and assume new and more responsibilities, and show fortitude, unflappability, and moral compass. Building strong institutional cultures requires adherence to seven critical values. First is academic freedom, which in most jurisdictions embodies two dimensions, the freedom of enquiry for faculty and students and the procedural and substantive autonomy of institutions. In the first instance, a faculty member should be able to teach or express scholarly views without fear of reprisals, and in the second an institution has the right to determine for itself on academic grounds how its core business of teaching and research is conducted. In many African countries and universities academic freedom in both senses is contested and often breached by pervasive authoritarian interventions and impulses by the state, administration, and governing boards. Second is shared governance, which refers to the participation and demarcation of rights and responsibilities in decision-making between faculty, management and governing boards. Typically, faculty is expected to exercise authority on academic matters such as the curriculum, instruction and degree requirements. As universities have become more complex and demands for accountability have increased, democratic organisational processes have been eroded, replaced by what critics call corporatisation and managerialism. It is critical to balance the management of the university as a complex organisation and the traditions and ethos of collegiality, participation and distributed power by maintaining what is called in South Africa cooperative governance. Third is diversity, equity and inclusion. Given their critical role as pathways for social mobility and leadership across all sectors, universities are increasingly expected to promote diversity, equity and inclusion at all levels and for all their constituencies. Inequalities of access, support and success are deeply entrenched across Africa’s and the world’s multicultural, multiracial and multiethnic, gendered, and class societies that are also marked by other forms of difference and discrimination. By providing opportunities for underrepresented groups and creating and sustaining an inclusive climate through their mission, values, policies and practices, universities promote inclusive excellence for institutional and national progress. Fourth, civility and collegiality. The academic bully culture, as Darla Twale and Barbara De Luca call it in their book by that title, has grown.13 Some call it academic mobbing.14 Incivility and intolerance in universities have several manifestations. At a macro level they reflect the frictions of increasing diversification of university stakeholders, growing external pressures for accountability, and the descent of political discourse into angry populisms. Student and faculty incivility are also fuelled by rising sense of entitlement, consumerist attitudes, emotional immaturity, stress, racism, tribalism, sexism, ageism, xenophobia, social media, and other pervasive social and institutional ills that universities must confront and address to foster healthier institutional climate. Fifth, universities must maintain their role as generative spaces in the rigorous search for truth. The ‘posts’ and the movement for decolonising knowledge have vigorously and rightly contested the epistemic architecture and metanarratives of the Eurocentric academy and its hegemonic knowledges. However, as we pluralise knowledges and universalisms, remake intellectual cultures, and transform our universities, we must resist the relativism of alternative facts, the nihilism of anti-science, and the solipsism of self-referentiality beloved by populist demagogues, many of them products of the world’s leading universities, as some critics noted of the neo-fascist Trumpists in the United States who live in a world of alternative facts. Sixth, effective communication is essential for building cohesive communities out of the university’s disparate constituencies that have divergent interests, priorities and preferences. Internally, these are students, faculty, staff, administrators and governance boards, and externally, prospective students and employees, alumni, parents, government, regulatory agencies, competitors, institutional partners, donors, the media, and the general public. This requires developing multiple communication channels, messages and styles tailored for different audiences to create dialogue and understanding. Good, transparent and regular internal communication fosters a sense of community, efficiency and the collective pursuit of institutional mission, vision and goals. Seventh, embracing social responsibility is vital for universities to eschew institutional naval-gazing for the higher purpose of social impact that can mobilise internal and external stakeholders. Universities are well placed to provide evidence-based knowledge solutions and innovations for society. Socially responsible universities need to embed public service in their missions, experiential learning in their curricula, and research that is responsive to pressing local, national, regional and global problems. They need to enhance their social ownership as public goods in tackling social inequities, and embrace research sharing with their communities.15 Financial sustainability requires pursuing seven strategies as well. The low financial capacities of many African universities is sobering. The Financial Year 2021 budget of the University of Illinois, where I spent the longest time in my academic career, is 6.7 billion, which is probably more than the combined budgets of public universities in several East African countries. In Kenya, in 2020–21, the government allocated the equivalent of 1.13 billion for all public higher education institutions, down from 1.53 billion in the previous year of which 1.06 billion was for salaries and only 70 million for infrastructural development. Research hardly features. First, public funding for higher education needs to be raised substantially if African countries are serious about improving the quality of human capital so essential for integrated and innovative sustainable development, and for them to turn the demographic explosion into a dividend rather than a disaster. The burial of the ghosts of structural adjustment programmes is long overdue. African governments need to develop innovative allocation mechanisms to universities encompassing clear funding formulas, performance contracts and competitive grants. The latter two should be open to both public and private universities. Second, establish differentiated tuition pricing and targeted student aid. Besides increasing spending per student, which is the lowest in the world, African governments and universities must develop targeted free or low-cost tuition for the neediest students who qualify for university studies, improve student loan recovery schemes, and make them income contingent. Private universities can do this through internal effective and sustainable student aid policies and external scholarships. Third, exercise prudent financial management. As I noted in the Framing Paper for the First Higher Education Summit held in Dakar in 2015, financial challenges facing higher education institutions require the adoption of more sophisticated and transparent budgeting models to ensure efficient utilisation of limited resources. The spectre of corruption that undermines the finances of some universities should also be ruthlessly tackled. Fourth, diversify revenue streams. Universities tend to have seven major sources of funding, namely: government subventions, student tuition, auxiliary services, income generating activities, research grants, philanthropic donations, and loans. African universities could increase income from auxiliary services by providing better accommodation for their students rather than leaving them captive to shoddy and dangerous neighbourhoods as has become the case on many campuses; undertaking entrepreneurial activities including consultancies, offering executive programmes, and establishing enterprises that leverage their expertise and innovations; consistently bringing in large research grants; and raising philanthropic donations from Africa’s rapidly expanding middle classes and high net worth individuals (HNWIs) with assets of more than 1 million. According to Frank Knight’s The Wealth Report 2021, in 2020 their numbers reached 231,000 (down from 251,511 in 2019), representing 0.48 per cent of the world’s total, while those ultrahigh net worth individuals (with assets of more than 30 million) reached 3,270 (up from 3,127 in 2019) accounting for 0.63 per cent of the world’s total.16 Collectively, African HNWIs own nearly 2 trillion. The few who give to universities prefer to donate to renowned universities in the global North than to their own countries. Indeed, African elites prefer to educate their children abroad than at home, just as they trek overseas for medical care. The national bourgeoisies of African countries tend to be among the least patriotic in the world in terms of building or supporting national high quality educational and health care facilities because they can readily access them in the wealthy countries. That is one of the unintended benefits of COVID-19: it underscored the importance of building such facilities and services at home for the elites and their children, who are socialised and pampered to be as un-African as possible, as they could no longer freely travel overseas. Fifth, create institutional mergers. There’s no doubt that Africa needs more universities, but they must be financially sustainable. Many of the public and private universities that have mushroomed in the last two decades are simply glorified high schools. For economies of scale in the higher education sector mergers are imperative even for the fiercely independent and often thinly disguised forprofit private universities. This has to be part of a strategic agenda for diversification and differentiation, accompanied by horizontal and vertical articulation of higher education institutions at national, regional and continental levels. Sixth, forge robust inter-institutional collaborations. University consortia will become increasingly necessary to promote quality education, facilitate cost-sharing and bargaining in the procurement of expensive technological infrastructures, instructional materials, talent development, and to facilitate the mobility of students, faculty, credit transfer, and the development of innovative inter-institutional programmes and practices. Seventh, strengthen external partnerships with other higher education institutions and non-academic sectors and organisations. Old patterns of asymmetrical internationalisation under which Africa was subordinated to Euroamerican institutional and epistemological systems must be replaced by strategic inclusion, mutuality, and co-creation of activities and initiatives, and humanising internationalisation by abandoning exploitation of international students who tend to be treated as ‘cash cows’.17 Also important are partnerships with the private sector which under-invests in skills and needs to complement government funding in promoting high-quality education and reducing the much-bemoaned skills gap that employers often complain about. However, universities have to be discerning in establishing public-private partnerships to ensure they are not exploited as has happened to some universities. Critical players also include African international and intergovernmental agencies that often play second fiddle to their foreign counterparts in funding university activities and formulating policies. In this article I have tried to share ideas on the nature, dynamics and possible futures of African higher education. Some of the data might be disconcerting, but it is not meant to disempower us, rather to enrage and energise us. I come from the radical tradition of the 1970s and 1980s honed in Southern Africa’s experiences of liberation struggles, that as we strive for better futures we must combine the pessimism of the intellect and optimism of the will, that is: there is need for coldhearted analysis of conditions as they are, and ironclad conviction of the agency we possess as human beings and social actors to bring about change. That is why I am neither an Afro-pessimist, nor an Afro-optimist, but an Afro-realist. Higher education is too important for Africa’s future to be held captive to haphazard interventions and superficial reforms. What is needed is fundamental transformation thanks, in part, to the massive disruptions of COVID-19. Studies show the returns on investment for education are much higher for society and individuals than any other form of investment. This applies to all levels, including tertiary, not just primary education as we were told by the misguided missionaries who propagated the neoliberal assault on universities during Africa’s ‘lost decades’ of the 1980s and 1990s with the connivance of the anti-intellectualist and anti-developmentalist political classes of many African states. I believe we – governments, the private sector, civil society and the universities working together – can remake the future of African higher education. Notes This article was first published on May 28, 2021 on the author’s Linke- dIn page. It is republished here with permission from the author. African Union, Agenda 2063, https://au.int/en/agenda2063. Michael Adaney, 2018, ‘The Afri- can Union’s Agenda 2063: Educa- tion and Its Realization’, in A. C. Onuora-Oguno, W. O. Egbewole and T. E. Kleven, eds, Education Law, Strategic Policy and Sus- tainable Development in Africa. Agenda 2063, New York: Palgrave Macmillan, pp. 181–97. Declaration and Action Plan from the First African Higher Education Summit on Revitalizing Higher Ed- ucation for Africa’s Future, https://www.trustafrica.org/images/Executive%20SummaryFINAL.pdf. Paul Tiyambe Zeleza, ‘COVID-19 and African universities – AAP dia- logue takeaways’, University World News, July 16, 2020, https://www.universityworldnews.com/post.php?story=20200714080656408. Awino Okech, David Mwam- bari and Funmi Olonisakin, 2021, ‘COVID-19 responses and human rights in selected African coun- tries’, Australian Journal of Hu- man Rights 26 (3): 549–55. ‘Tracking COVID-19 vaccinations worldwide’, CNN, https://edition.cnn.com/interactive/2021/health/ global-covid-vaccinations/. Wagdy Sawahel, ‘COVID-19: col- laborate or perish – A roadmap for research’, University World News, January 21, 2021, https://www.universityworldnews.com/post.php?story=20210118054151358. Wagdy Sawahel, ‘Protecting Af- rica from becoming vaccine test lab’, University World News, January 28, 2021, https://www.universityworldnews.com/post. php?story=20210126190108880. Segue Ogunwale, ‘Industry-aca- demia collaboration tested during COVID-19’,UniversityWorldNews, February 4, 2021, https://www.universityworldnews.com/post. php?story=20210201045446705. Susan Grajek and the 2020–2021 EDUCAUSE IT Issues Panel, ‘Top IT issues, 2021: emerging from the pandemic’, EDUCAUSE, Novem- ber 2, 2020, https://er.educause.edu/articles/2020/11/top-it-issues- 2021-emerging-from-the-pandemic. Some of these are derived from Ginny Schaefer Horvath and Maya Ranchod Kirkhope, ‘Sharpening the lens for hiring leaders’, https://academicsearch.org/wp-content/uploads/formidable/8/ASI- 2020-Vision-Article.pdf. Kristen A. Frey Knepp, 2012, ‘Understanding student and fac- ulty incivility in higher education’, Journal of Effective Teaching 12 (1), 33–46; Chula King and Chris Piotrowski, 2015, ‘Bullying of educators by educators: incivility in higher education’, Contempo- rary Issues in Education Research 8 (4): 257–62; Daria J. Twale and Barbara M. De Luca, 2008, Fac- ulty Incivility: The Rise of the Aca- demic Bully Culture and What to Do about It, San Francisco, CA: Jossey Bass. Even Seguin, ‘Academic mobbing, or how to become campus tormentors’, University Affairs/ Affaires universitaires, September 19, 2016, https://www.university-affairs.ca/opinion/in-my-opinion/academic-mobbing-become-cam-pus-tormentors/. Maina Waruru and Wachira Kigotho, ‘Social responsibility should be in missions of univer- sities’, University World News, February 11, 2021, https://www.universityworldnews.com/post.php?story=20210209050531590; Wachira Kigotho, ‘Recalibrating the social ownership of our uni- versities’, University World News, February 11, 2021, https://www.universityworldnews.com/post.php?story=20210209073456189; Wachira Kigotho, ‘Universities urged to be drivers of societal solidarity’, University World News, February 5, 2021, https://www.universityworldnews.com/post.php?story=20210205073334340; Nic Mitchell, ‘Treat communities as partners to improve social impact’, University World News, January 29, 2021, https://www.universityworldnews.com/post.php?story=20210129084451125. Frank Knight, The Wealth Report: The Global Perspective on Prime Property and Investment 2021, https://content.knightfrank.com/research/83/documents/en/the-wealth-report-2021-7865.pdf. John K. Hudzik, ‘How to strengthen internationalisation post- COVID-19’, University World News, June 6, 2020, https://www.universityworldnews.com/post.php?story=20200605072319401; Fay Patel, ‘Humanizing international higher education’, University World News, September 5, 2020, ww.